TRANSLATING A RELIGIOUS BOOK “Why I am a Muslim” PROBLEMS AND CHALLENGES - rosalia, Mella; Rochmah, Siti; Supartini, Nai (PROJECT (Professional Journal of English Education), 2019)
The idea translated is a concept or message that the author writes in his writings. Translating Books with religious nuances is more than just transferring the concept or storyline, because it has a high sensibility, which is loaded with sacred meanings that can only be understood well by adherents who really live the expression and means in earnest beside learn and explore the values of religion and belief earlier, but it should also be able to describe messages that can be affected by culture or literal. This article describes the authors' experiences when translating English religious nuances book containing personal experiences from MS. Asma Gull Hasan concerns grief as a minority Muslim group in America. Computer Assisted Translation (CAT) Tool using aid translators to edit, manage and store translations.